Tuning spin current injection at ferromagnet-nonmagnet interfaces by molecular design - Wittmann, Angela; Lami, Vincent; Vaynzof, Yana (Physical review letters, 2020)
There is a growing interest in utilizing the distinctive material properties of organic semiconductors for spintronic applications. Here, we explore the injection of pure spin current from Permalloy into a small molecule system based on dinaphtho[2,3-b:2,3-f]thieno[3,2-b]thiophene (DNTT) at ferromagnetic resonance. The unique tunability of organic materials by molecular design allows us to study the impact of interfacial properties on the spin injection efficiency systematically. We show that both the spin injection efficiency at the interface and the spin diffusion length can be tuned sensitively by the interfacial molecular structure and side chain substitution of the molecule.
Gesehen am 02.04.2020